Proceso de atención de enfermería en pacientes con tuberculosis aplicando el modelo de Dorotea Orem, centro de salud san Camilo. Quevedo. Periodo. enero - abril 2023. - Espín Rosero, Roxana Narcisa (2023)
Introduction: Tuberculosis is an infectious disease that mainly affects the lungs but can also affect other organs, it is a public health problem that affects all citizens equally, regardless of gender, age, race or income level. Objective: To apply the nursing care process in patients with tuberculosis based on the Dorothea Orem model to improve the self-care of outpatients. Methodology: The level of research used is descriptive, with a cross-sectional design, under the quantitative approach, the basic research modality was bibliographical and field type in which resources such as articles, theses and publications were used, working with 18 patients, which is 100% of the total population, and for data processing the statistical program SPSS V25 was used. Results: The database was presented in tables, and the main results are presented in a descriptive manner, each table has comparisons between the criteria of various authors, based on these tables, 8 nursing plans were prepared based on the Dorothea Orem model, among the main diagnoses are: risk of infection, ineffective self-management of health and tendencies to adopt risky behaviors for health. Conclusion: The application of the nursing process in patients with tuberculosis in the "San Camilo Health Center" was statistically significant. KEY WORDS: Tuberculosis, nursing care process, self-care, nursing care.